A super-efficiency data envelopment analysis (DEA) sensitivity analysis algorithm for fixed input allocation - Bacus, Mary Grace Berco (2008)
Data envelopment analysis (DEA) is a mathematical programming technique to evaluate the efficiency of similarly operating entities relative to each other in terms of consuming inputs to produce outputs. Nevertheless, hardly any DEA literature has focused on the subject of fixed input allocation or incorporated minimization of the number of relatively inefficient entities in an organization to DEA sensitivity analysis. The study used the super-efficiency DEA (SE-DEA) sensitivity analysis findings of Zhu (2001) to produce an algorithm for adjusting the distribution of fixed resources to minimize the number of inefficient units. To formulate the SE-DEA algorithm, the paper arrived at propositions and presented formalized rules to increase rate and decrease rate for reallocation of a fixed input. To illustrate the developed algorithm numerically, it was implemented to redistribute each of a charity foundation?s fixed yearly financial resources from 2003 to 2006 to its quarterly programs. Results showed that the SE-DEA sensitivity analysis algorithm is a promising approach to fixed input allocation for optimizing relative efficiency in an organization
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2008
Keywords: Efficiency analysis; Fixed input allocation; Super-efficiency algorithm; DEA (Data Envelopment Analysis); SE (Super-efficiency); Mathematical programming techniques; SE-DEA (Super-efficiency-Data envelopment analysis) algorithms